Return to the Gift in Sudanese Law and Islamic Jurisprudence - Ibrahim Bashir Abdullah Idris (International Journal of Law Research and Studies, 2024)
The gift (Hibah) contract is one of the contracts that transfers ownership, but it differs from the sale contract as a contract transferring ownership in that it does not complete or transfer ownership from the Donor to the Donee except after the Donee takes possession of the gifted thing. Disagreement has arisen among Islamic Sharia jurists over the possibility of the donor to take back his gift, whether before or after receipt. The study addressed the topic of revocation of the gift (Hibah) in Sudanese law and in the four schools of jurisprudence (Hanafi, Maliki, Shafi’i, and Hanbali). Among the results, Sudanese law permitted the Donor to retract his gift (Hibah) before the Donee took possession of the gifted thing, and after receipt, Sudanese law permitted revocation of the gift (Hibah) by consent or judgment. As for Islamic jurisprudence, it became clear from the study that the Donor has the right to reclaim the gift (Hibah) before taking possession according to the majority of Hanafi, Shafi’i and Hanbali jurists. The Maliki’s differ with the majority in that they restricted the permissibility of Returning the gift (Hibah) before taking possession of the gift is for the child. Other than that, it is not permissible to return. As for after receipt, the majority of Maliki, Shafi’i, and Hanbali jurists permitted revocation of the gift (Hibah) if it was for the child. The Hanafi’s differed from the majority in that they permitted revocation of the gift (Hibah) after receipt even if it was for someone other than the child, unless there is something that prevents recourse to the gift (Hibah) in their doctrine.